Pelatihan Soft Skills dan Legalitas Usaha sebagai Strategi Peningkatan Kapasitas UMKM - Pranogyo, Antaiwan Bowo; Tarsono, Ono; Hendro, Junaidi; Sumampouw, Ruland Willy Jack; Ichsan, Muhammad; Suryono, Dwi Windu (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
This community engagement program aimed to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in North Jakarta through training on business legality and Soft Skills. The program targeted PKK cadres and entrepreneurs supported by the local Office for Women Empowerment (Sudin PPAPP). The training emphasized the importance of legal documents such as NIB, NPWP, PIRT, Halal Certification, IPR, and BPOM permits, which are often overlooked by MSMEs. Using a participatory and practical approach, the sessions included OSS-based licensing simulations, financial literacy tools, and communication skill development. Results showed that 70% of participants demonstrated increased legal awareness and began the legalization process for their businesses. This initiative supports the Jakpreneur program’s goals of formalizing and strengthening MSMEs, while also fulfilling the university’s community service mission. The program is expected to contribute to a more inclusive, legally compliant, and competitive MSME ecosystem in Indonesia.